Strategies for recycling and valorization of grape marc. (19th May 2019) - Gómez-Brandón, María; Lores, Marta; Insam, Heribert; Domínguez, Jorge
Abstract: Grapes are one of the most cultivated fruit crops worldwide. Either for wine or juice production, grape processing generates a large amount of residues that must be treated, disposed of or reused properly to reduce their pollution load before being applied to the soil. In this review, a special focus is given to the treatment and valorization of the winemaking by-product like grape marc via anaerobic digestion, composting and vermicomposting at laboratory, pilot, and industrial scales. The impact of the final products (digestates, composts, and vermicomposts) on soil properties is briefly addressed. Moreover, the role of grape marc and seeds as a valuable source of natural phytochemicals that include polyphenols and other bioactive compounds of interest for pharmaceutical, cosmetic, and food industries is also discussed. This is of paramount importance given the fact that sustainability requires the use of management and valorization strategies that allow the recovery of valuable compounds (e.g. antioxidants) with minimum disposal of waste streams.